Asparagine levels in the cerebrospinal fluid of children with acute lymphoblastic leukemia treated with pegylated-asparaginase in the induction phase of the AIEOP-BFM ALL 2009 study - Rizzari, Carmelo; Lanvers-Kaminsky, Claudia; Valsecchi, Maria Grazia; Ballerini, Andrea; Matteo, Cristina; Gerss, Joachim; Wuerthwein, Gudrun; Silvestri, Daniela; Colombini, Antonella; Conter, Valentino; Biondi, Andrea; Schrappe, Martin; et al. (Haematologica, 2019)
Asparagine levels in cerebrospinal fluid and serum asparaginase activity were monitored in children with acute lymphoblastic leukemia treated with pegylated-asparaginase. The drug was given intravenously at a dose of 2,500 IU/m2 on days 12 and 26. Serum and cerebrospinal fluid samples obtained on days 33 and 45 were analyzed centrally. Since physiological levels of asparagine in the cerebrospinal fluid of children and adolescents are 4-10 μmol/L, in this study asparagine depletion was considered complete when the concentration of asparagine was ≤0.2 μmol/L, i.e. below the lower limit of quantification of the assay used. Over 24 months 736 patients (AIEOP n=245, BFM n=491) and 903 cerebrospinal fluid samples (n=686 on day 33 and n=217 on day 45) were available for analysis. Data were analyzed separately for the AIEOP and BFM cohorts and yielded superimposable results. Independently of serum asparaginase activity levels, cerebrospinal fluid asparagine levels were significantly reduced during the investigated study phase but only 28% of analyzed samples showed complete asparagine depletion while relevant levels, ≥1 μmol/L, were still detectable in around 23% of them. Complete cerebrospinal fluid asparagine depletion was found in around 5-6% and 33-37% of samples at serum asparaginase activity levels <100 and ≥ 1,500 IU/L, respectively. In this study cerebrospinal fluid asparagine levels were reduced during pegylated-asparaginase treatment, but complete depletion was only observed in a minority of patients. No clear threshold of serum pegylated-asparaginase activity level resulting in complete cerebrospinal fluid asparagine depletion was identified. The consistency of the results found in the two independent data sets strengthen the observations of this study. Details of the treatment are available in the European Clinical Trials Database at https://www.clin-icaltrialsregister.eu/ctr-search/trial/2007-004270-43/IT.
Keywords: Germany; akutní lymfatická leukemie; Female; Infant; dítě; předškolní dítě; ženské pohlaví; monitorování léčiv; Adolescent; Polyethylene Glycols; asparaginasa; lidé; Italy; Austria; Itálie; Německo; polyethylenglykoly; asparagin; Male; kojenec; Czech Republic; Child, Preschool; Drug Monitoring; Asparaginase; Česká republika; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Child; mužské pohlaví; Asparagine; mladiství; Rakousko; Humans